Development of Communicative Production Competencies and Textual Understanding (Docentes 2.0 Journal, 2020)
The following research was carried out under the observation, diagnosis, as well as the planning and analysis of a process that aims to strengthen the development of production communication skills such as textual comprehension in elementary school students. It began with a diagnosis of the students' reading-writing level, then the design of a pedagogical intervention proposal based on these results; subsequently, the effect of the intervention proposal on the processes of text comprehension - textual production was evaluated. The research was developed under the qualitative approach and action research design, since they are the most successful in education because teachers have the possibility of inquiring about their own pedagogical exercise; analyze and understand it, as, the main instrument: self-reflection. In turn, ICTs were involved, with striking activities that not only allowed the acquisition of necessary information, but also active learning through the development of skills such as: consultation and information management, development of the critical level, resolution of situations and decision making. decisions, creativity, and innovation. As a result of the above, various activities and strategies were designed that made it possible to strengthen, expand the lexicon, work on grammatical aspects, coherence, cohesion applied to different kinds of texts, which contributed to the improvement of these processes. In conclusion, the intervention implemented notably improved the performance of the students, had significant effects on academic performance, improved the reading-writing process, generated the habit of reading, in turn allowed a dynamic participation of the entire educational community.
Keywords: Active learning; production; textual understanding; TIC